Blood group discrepancies at a tertiary care centre – analysis and resolution. (11th December 2013) - Kaur, G.; Kaur, P.; Basu, S.; Kaur, R.
Summary Introduction The ABO system is the most important of all blood group systems in transfusion practice. ABO grouping is a simple, accurate, and precise procedure and to be considered valid, the results of cell grouping and serum grouping should agree. The aim of this study was to assess the cause of discrepancies and its implication in transfusion practice. Methods This study was performed between January 2010 and May 2013. We analyzed ABO discrepancies which were detected serologically in blood donors, where a result of cell grouping and serum grouping was discordant. Confirmation of subgroups was carried out by adsorption and elution technique. Saliva of these donors was also tested for A, B, and H antigens by inhibition tests. Results Twenty‐eight blood group discrepancies were observed in 44 425 blood groups tested during the study period, thus giving an overall frequency of 0.06%. Technical errors leading to blood group ABO discrepancy were noticed in five cases. Sample‐related problems that affect red‐cell testing were observed in twenty cases, and the most common cause of ABO discrepancies in this category was subgroups of A and B. ABO discrepancies that affect the serum testing included the presence of additional antibodies other than anti‐A and anti‐B. Conclusion It is imperative to recognize discrepant results and resolve them. Correct blood typing and labeling of an individual are essential to prevent ABO incompatibility.